Long-Term Consequences of Placental Vascular Pathology on the Maternal and Offspring Cardiovascular Systems - Marisa Benagiano; Salvatore Mancuso; Jan J. Brosens; Giuseppe Benagiano (Biomolecules, 2021)
Over the last thirty years, evidence has been accumulating that Hypertensive Disorders of Pregnancy (HDP) and, specifically, Preeclampsia (PE) produce not only long-term effects on the pregnant woman, but have also lasting consequences for the fetus. At the core of these consequences is the phenomenon known as defective deep placentation, being present in virtually every major obstetrical syndrome. The profound placental vascular lesions characteristic of this pathology can induce long-term adverse consequences for the pregnant woman’s entire arterial system. In addition, placental growth restriction and function can, in turn, cause a decreased blood supply to the fetus, with long-lasting effects. Women with a history of HDP have an increased risk of Cardiovascular Diseases (CVD) compared with women with normal pregnancies. Specifically, these subjects are at a future higher risk of: Hypertension; Coronary artery disease; Heart failure; Peripheral vascular disease; Cerebrovascular accidents (Stroke); CVD-related mortality. Vascular pathology in pregnancy and CVD may share a common etiology and may have common risk factors, which are unmasked by the “stress” of pregnancy. It is also possible that the future occurrence of a CVD may be the consequence of endothelial dysfunction generated by pregnancy-induced hypertension that persists after delivery. Although biochemical and biophysical markers of PE abound, information on markers for a comparative evaluation in the various groups is still lacking. Long-term consequences for the fetus are an integral part of the theory of a fetal origin of a number of adult diseases, known as the Barker hypothesis. Indeed, intrauterine malnutrition and fetal growth restriction represent significant risk factors for the development of chronic hypertension, diabetes, stroke and death from coronary artery disease in adults. Other factors will also influence the development later in life of hypertension, coronary and myocardial disease; they include parental genetic disposition, epigenetic modifications, endothelial dysfunction, concurrent intrauterine exposures, and the lifestyle of the affected individual.